Cyclopropenes for the Synthesis of Cyclopropane‐Fused Dihydroquinolines and Benzazepines. Issue 13 (10th September 2015) - Luo, Hui‐Xin; Niu, You‐Hong; Cao, Xiao‐Ping; Ye, Xin‐Shan
Abstract An efficient method for the construction of cyclopropane‐fused dihydroquinolines was established by a novel Povarov‐type three‐component reaction of aromatic aldehydes, anilines and cyclopropenes in the presence of trifluoromethanesulfonic acid. The reaction proceeded in a regioselective and diastereoselective manner. Furthermore, the dihydroquinolines were smoothly converted to benzazepine derivatives via a ring opening/isomerization sequence, further expanding the synthetic scope.